Desain Sistem Informasi Evaluasi Diri Program Studi Teknik Informatika Politeknik Caltex Riau - Juni Nurma Sari; Wawan Yunanto (UIN Sultan Syarif Kasim Riau, 2011)
Self Evaluation is part of qualty assurance proses of high education institution. The objective of self evaluation is continous improvement. There are two kind evaluation that is internal evaluation and external evaluation. Internal evaluation done by civitas academica inside department. External evaluation done by Badan Akreditasi Nasional Perguruan Tinggi (BAN-PT). Internal evaluation is preparation for external evaluation. Self evaluation need three years academic record. That data must be collected from BAAK (Badan Administration Akademik dan Kemahasiswaan) , IT deparment, staf and human resource department. It is difficult, because sometimes data is not consistent. Self Evaluation Information System would be a solution. It can make self evaluation process more easier also complitness of acreditation standard, because data already prepared. This Information System is development of Academic Information System PCR, with another data adds on such as facility, lecturer, quality assurance, alumni etc. That data appropriate with standar acreditation(borang akreditasi) which used as reference Self Evaluation Information System design. Information System will be build using My SQL and PHP. Hopefully, Self Evaluation Information System can make the proses of self evaluation internal or external more effisien, so the continous improvement will be reached faster. Keyword : Information System, Sel Evaluation, Acreditation Standard, My SQL, PHP